Sources, fates, toxicity, and risks of trifluoroacetic acid and its salts: Relevance to substances regulated under the Montreal and Kyoto Protocols - Bornman, Janet (2016)
Trifluoroacetic acid (TFA) is a breakdown product of several hydrochlorofluorocarbons (HCFC), regulated under the Montreal Protocol (MP), and hydrofluorocarbons (HFC) used mainly as refrigerants. Trifluoroacetic acid is (1) produced naturally and synthetically, (2) used in the chemical industry, and (3) a potential environmental breakdown product of a large number (>1 million) chemicals, including pharmaceuticals, pesticides, and polymers. The contribution of these chemicals to global amounts of TFA is uncertain, in contrast to that from HCFC and HFC regulated under the MP. TFA salts are stable in the environment and accumulate in terminal sinks such as playas, salt lakes, and oceans, where the only process for loss of water is evaporation. Total contribution to existing amounts of TFA in the oceans as a result of the continued use of HCFCs, HFCs, and hydrofluoroolefines (HFOs) up to 2050 is estimated to be a small fraction (<7.5%) of the approximately 0.2 µg acid equivalents/L estimated to be present at the start of the millennium. As an acid or as a salt TFA is low to moderately toxic to a range of organisms. Based on current projections of future use of HCFCs and HFCs, the amount of TFA formed in the troposphere from substances regulated under the MP is too small to be a risk to the health of humans and environment. However, the formation of TFA derived from degradation of HCFC and HFC warrants continued attention, in part because of a long environmental lifetime and due many other potential but highly uncertain sources.